Zasoby Biblioteki Polskiej w Londynie - przegląd polskich tytułów prasy emigracyjnej dla inteligencji = The resources of the Polish Library in London - a review of Polish émigré press titles for the Polish intelligentsia - Chwastyk-Kowalczyk, Jolanta (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article addresses the presence of a selection of Polish emigre periodicals published abroad and intended for the intelligentsia, mainly in the UK, from the Second World War to the present, through the functioning of the Polish Library in London. The author discusses periodicals edited by experienced journalists before the war, revived in Paris and moved to London, as well as the newly formed newspapers, military magazines, socio-cultural, literary and artistic, and scientific periodicals in the United Kingdom. In addition to magazines established by the "undeterred" generation, the author presents magazines created by the generation of Poles from the EU, emphasizing the role of the influential "Nowy Czas" ("New Time") formed in London in 2006. The author analyzes the phases of emergence and development of the Polish Library in London from 1942 to today, along with changes to the profile for the acquisition of collections, and to the objectives, activities and role of this institution in building and integrating the national identity of our compatriots in the United Kingdom.
Keywords: biblioteki; biblioteki emigracyjne; biblioteki polskie; Biblioteka Polska w Londynie; emigracja; prasa; prasa emigracyjna; prasa polska; inteligenci; libraries; emigration libraries; Polish libraries; Polish Library in London; emigration; press; emigration press; polish press; intelligentsia